Causal effect of serum 25-hydroxyvitamin D levels on low back pain: A two-sample mendelian randomization study - Jiang, Xiaojuan; Zhou, Ruihao; He, Yi; Zhu, Tao; Zhang, Weiyi (Frontiers in Genetics, 2022)
Background: Previous observational studies have suggested the involvement of 25-hydroxyvitamin D [25(OH)D] in chronic pain. However, whether the 25(OH)D is a novel target for management, the causality remains unclear. Methods: A two-sample Mendelian randomization (MR) study was conducted to identify the causal association between 25(OH)D and low back pain (LBP). The primary analysis was revealing causality from serum 25(OH)D level (n = 417,580) on LBP (21,140 cases and 227,388 controls). The replicated analysis was performing MR estimates from circulating 25(OH)D concentration (n = 79,366) on LBP experienced last month (118,471 cases and 343,386 controls). Inverse variance weighted (IVW) was used as the main analysis. In addition, we used weighted median and MR-Egger to enhance the robustness. Sensitivity analysis was conducted to evaluate the robustness of MR results. Results: IVW estimation indicated strong evidence that higher serum 25(OH)D levels exerted a protective effect on LBP (OR = 0.89, 95% CI = 0.83–0.96, p = 0.002). Similar trends were also found in replicate analysis (OR = 0.98, 95% CI = 0.96–1.00, p = 0.07). After meta-analysis combining primary and replicated analysis, the causal effect is significant (p = 0.03). Sensitivity analysis supported that the MR estimates were robust. Conclusion: In our MR study, genetically increased serum 25(OH)D levels were associated with a reduced risk of LBP in the European population. This might have an implication for clinicians that vitamin D supplements might be effective for patients with LBP in clinical practice.